A Clinical Study of Noninvasive Assessment of Lung Lesions in Patients with Coronavirus Disease-19 (COVID-19) by Bedside Ultrasound - Lu, Wuzhu; Zhang, Shushan; Chen, Binghui; Chen, Jiaxin; Xian, Jianzhong; Lin, Yuhong; Shan, Hong; Su, Zhong Zhen (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose This study was conducted to explore the clinical value of noninvasive assessment of bedside ultrasound in the diagnosis of lung lesions of Coronavirus Disease-19.Methods In this retrospective study, 30 patients with Coronavirus Disease-19 admitted to our hospital from January 18 to February 5, 2020, were selected as the research subjects. All cases were examined by lung ultrasound and CT. Lung lesions were reviewed by blinded observers, with imaging scores being used to analyze the ultrasound findings of lung lesions in patients with Coronavirus Disease-19 and with chest CT being used as the reference standard. The clinical value of ultrasound in the noninvasive assessment of lung lesions was evaluated.Results Lung ultrasound signs in patients with Coronavirus Disease-19 were mainly manifested as interstitial pulmonary edema (90.0 %, 27/30) and pulmonary consolidations (20.0 %, 6/30). The lung lesions were mainly distributed in the subpleural and peripheral pulmonary zones. The lower lobe and the dorsal region had a greater tendency to be involved. There was moderate agreement (Kappa = 0.529) between the noninvasive assessment of bedside ultrasound for lung lesions in patients with Coronavirus Disease-19 and CT. The ultrasound scores to evaluate mild, moderate and severe lung lesions exhibited sensitivity of 68.8 % (11/16), 77.8 % (7/9), 100.0 % (2/2), specificity of 85.7 % (12/14), 76.2 % (16/21), 92.9 % (26/28), and diagnostic accuracy of 76.7 % (23/30), 76.7 % (23/30), 93.3 % (28/30), respectively. The follow-up dynamic ultrasound examination showed that the condition of all patients worsened gradually, with the ultrasound scores of lung lesions increasing to varying degrees.Conclusion Though the diagnostic efficacy of bedside ultrasound is relatively low for mild to moderate patients, it is high for severe patients. Bedside ultrasound has important clinical significance for noninvasive assessment and dynamic observation of lung lesions in patients with Coronavirus Disease-19, which is worth further consideration.
Keywords: COVID-19; ultrasound; CT; LUS